Capital and labour (mis)allocation in the euro area: some stylized facts and determinants - Elisa Gamberoni; Claire Giordano; Paloma Lopez-Garcia (European Central Bank (ECB), 2016)
We analyse the evolution of capital and labour (mis)allocation across firms in five euro-area countries (Belgium, France, Germany, Italy and Spain) and eight main sectors of the economy during the period 2002-2012. Three key stylized facts emerge. First, in all countries with the exception of Germany, capital allocation has worsened over time whereas the efficiency of labour reallocation has not changed significantly. Second, the observed increase in capital misallocation has been particularly severe in services as opposed to industry. Third, misallocation of both labour and capital dropped in all countries in 2009 and again for some country-sectors in 2011-2012. We next take stock of the possible drivers of input misallocation dynamics in a standard panel regression framework. Controlling for demand conditions and for the initial level of misallocation, heightened uncertainty, restrictive bank credit standards and tight product and labour market regulation are found to have boosted input misallocation, whereas the Great Recession per se exerted a cleansing effect.
Keywords: D24; D61; O47; 330; allocative efficiency; capital; Great Recession; labour; total factor productivity